Pengembangan Wisata Pesisir Berbasis Ekowisata Di Pantai Sadranan Kabupaten Gunungkidul - Fahmi Fadholi Ramadhan; I Made Adhi Gunadi; Meizar Rusli (STIE Pariwisata API Yogyakarta, 2024)
The importance of developing ecotourism is so that tourist attractions can be sustainable and have a positive impact on the community's economic sector, ecological sustainability and social benefits in the form of community empowerment. Ecotourism has five principles, namely nature-based, ecological sustainability, environmental education, benefits to the surrounding community and visitor satisfaction. This research aims to identify the application of ecotourism principles in the development of coastal tourism and analyze the development of coastal ecotourism at Sadranan Beach. The data obtained was analyzed using SWOT analysis to determine internal factors, namely strengths and weaknesses, as well as external factors, namely opportunities and threats. The research results show that of the five principles of ecotourism, Sadranan Beach tourism management has implemented four principles of ecotourism, namely nature-based, environmental education, benefits to the surrounding community and visitor satisfaction. There is one principle that has not been implemented optimally, namely ecological sustainability. According to the results of the SWOT analysis, the development of Sadranan Beach can be carried out with a (S-O) strategy, namely using strengths by taking advantage of opportunities. The (S-O) strategy includes ecotourism-based development, maintaining biodiversity and optimizing the role of the community in tourism development.